Flowing Gas Experiments Reveal Mechanistic Details of Interfacial Reactions on a Molecular Level at Knudsen Flow Conditions - Iannarelli, Riccardo; Ludwig, Christian; Rossi, Michel J. (Frontiers in Astronomy and Space Sciences, 2022)
Knudsen flow experiments and its interpretation in terms of adsorption/desorption kinetics as well as quantitative uptake on substrates of interest is presented together with the description of critical design parameters of the Knudsen Flow Reactor (KFR). Hitherto focused almost exclusively on the uptake phase exposing a virgin substrate to interacting gases, we now extend the experiment and its interpretation to the desorption phase at ambient temperature. We present analytical expressions for different experimental situations in terms of adsorption (ka), desorption (kd) and effusion (ke) rate constants. The measurement of kd leads to surface residence times (1/kd) obtained under the same experimental conditions as the uptake (ka) that results in the determination of the Langmuir equilibrium constant KL = ka/kd. We emphasize the interaction of semivolatile organic probe gases and small polar molecules with amorphous carbon and mineral dust materials at ambient temperatures. The latter leads to a molecular characterization scheme based on the use of up to ten different reactive probe gases. After saturation of the uptake of each probe gas this results in a reactivity map of the interface. Several examples are used to underline the broad applicability of the technique such as the silver/air (Ag) interface and the reactivity of TiO2 materials towards uptake of CO2 and CH3OH. Following characterization of several types of amorphous carbon a model incorporating several structural elements in agreement with the reactive gas titration is proposed. For instance, an interface that is at the same time weakly basic and strongly reducing is composed of pyrones and hydroquinones whose simultaneous occurrence leads to stable free radicals that may play a role in atmospheric chemistry (EPFR). The question is raised what makes an interface hydrophobic in terms of surface functional groups when interacting with small polar molecules such as H2O(D2O), HCl, NO2 and NH2OH. Multidiagnostic studies of heterogeneous reactions are enabled using stirred-flow reactors (SRF) that are a logical extension of the KFR approach thus relaxing the Knudsen flow requirements. Previous work using SRF on low-temperature substrates such as H2O ices is highlighted that may be of interest to the exoplanetary and space sciences community.